Optically Inspired Nanomagnonics with Nonreciprocal Spin Waves in Synthetic Antiferromagnets. Issue 9 (16th January 2020) - Albisetti, Edoardo; Tacchi, Silvia; Silvani, Raffaele; Scaramuzzi, Giuseppe; Finizio, Simone; Wintz, Sebastian; Rinaldi, Christian; Cantoni, Matteo; Raabe, Jörg; Carlotti, Giovanni; Bertacco, Riccardo; Riedo, Elisa; et al.
Abstract: Integrated optically inspired wave‐based processing is envisioned to outperform digital architectures in specific tasks, such as image processing and speech recognition. In this view, spin waves represent a promising route due to their nanoscale wavelength in the gigahertz frequency range and rich phenomenology. Here, a versatile, optically inspired platform using spin waves is realized, demonstrating the wavefront engineering, focusing, and robust interference of spin waves with nanoscale wavelength. In particular, magnonic nanoantennas based on tailored spin textures are used for launching spatially shaped coherent wavefronts, diffraction‐limited spin‐wave beams, and generating robust multi‐beam interference patterns, which spatially extend for several times the spin‐wave wavelength. Furthermore, it is shown that intriguing features, such as resilience to back reflection, naturally arise from the spin‐wave nonreciprocity in synthetic antiferromagnets, preserving the high quality of the interference patterns from spurious counterpropagating modes. This work represents a fundamental step toward the realization of nanoscale optically inspired devices based on spin waves. Abstract : Wavefront engineering, focusing, and multibeam interference of nonreciprocal spin waves are demonstrated by using spin‐texture‐based magnonic nanoantennas in synthetic antiferromagnets. Scanning transmission X‐ray microscopy experiments show the controlled emission and propagation of short‐wavelength spin waves for a distance of several wavelengths. Micromagnetic modeling of the angular‐dependent nonreciprocal spin‐wave modes in synthetic antiferromagnets and excitation mechanism supports the conclusions.